2021
DOI: 10.1002/qute.202000135
|View full text |Cite
|
Sign up to set email alerts
|

Topological Nature of High Temperature Superconductivity

Abstract: The key to unraveling the nature of high‐temperature superconductivity (HTS) lies in resolving the enigma of the pseudogap state. The pseudogap state in the underdoped region is a distinct thermodynamic phase characterized by nematicity, temperature‐quadratic resistive behavior, and magnetoelectric effects. Till present, a general description of the observed universal features of the pseudogap phase and their connection with HTS is lacking. The proposed work constructs a unifying effective field theory capturi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Our results also raise the question of whether the origin of V-shape conductance spectra is due to d-wave pairing as in the case of cuprates, or simply due to electronic disorder. Notably, the 3D superinsulator phase has been conjectured to be associated with the pseudogap phase of high-temperature superconductors (52). Very recently, numerical calculations have suggested that a disordered superconductor driven through the 3D Anderson transition shares some of the 2D phenomenology, including strong spatial fluctuations and enhancements of the order parameter, although only in the weak-coupling limit, and specific connections to local variables accessible via STM/STS are out of reach (53).…”
Section: Physicsmentioning
confidence: 99%
“…Our results also raise the question of whether the origin of V-shape conductance spectra is due to d-wave pairing as in the case of cuprates, or simply due to electronic disorder. Notably, the 3D superinsulator phase has been conjectured to be associated with the pseudogap phase of high-temperature superconductors (52). Very recently, numerical calculations have suggested that a disordered superconductor driven through the 3D Anderson transition shares some of the 2D phenomenology, including strong spatial fluctuations and enhancements of the order parameter, although only in the weak-coupling limit, and specific connections to local variables accessible via STM/STS are out of reach (53).…”
Section: Physicsmentioning
confidence: 99%
“…It thus occurs as the temperature compares with the coupling energy, and our estimate gives T c = O 10 2 K for a typical granule size of O(1) nm. We stress that these purely magnetic monopoles are different from the dyons in the pseudogap condensate 4 excitations which become stable since electron pairing reduces their repulsive energy and hence the total energy of the system. The pseudogapresiding monopoles are the endpoints of Josephson-like vortices residing in the granular array.…”
mentioning
confidence: 93%
“…A field-theoretical approach establishing the long sought unified theory of HTS and accounting for all universal features within the superconducting dome and in the pseudogap state in a consistent whole 4 , stemmed from the topological gauge theory of the SIT 24,26 and its generalization to three dimensions 27 . A fundamental mechanism of the HTS was identified as the formation of a condensate of dyons, electrically charged magnetic monopoles 4 . The superconducting state is a coexistence phase of dyon and pure charge condensates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The monopoles that we consider carry both the electric charge 2e and magnetic charge π/e (h/2e in physical units) and are called dyons. The topological theory of high-temperature superconductivity [16] establishes that the pseudogap state is the state harboring a condensate of dyons and that the charges carrying the electric current in this state are stable symmetryprotected fermionic edge dyons. We propose that edge dyons can be detected by measuring magnetic and electric fields that encircle currents carried by these excitations.…”
Section: Introductionmentioning
confidence: 99%